Influencia de la implementación de un sistema brt en la calidad del aire: caso de estudio Bogotá (2020)
One of the major environmental problems is air pollution product of the interaction of emissions from natural and anthropogenic sources, the latter being produced by industry, services or transportation. The implementation of the BRT Transmilenio system, accompanied by the constant remodeling of the vehicle fleet with better EURO standards, provides great opportunities in mitigating air pollution from mobile sources of public transport.